2015
DOI: 10.1165/rcmb.2014-0354oc
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Ninjurin1 to Toll-Like Receptor 4 Signaling and Systemic Inflammation

Abstract: Nerve injury-induced protein (Ninjurin [Ninj]) 1 is an adhesion molecule originally identified in Schwann cells after nerve injury, whereas it is also expressed in leukocytes, epithelium, endothelium, and various organs, and is induced under inflammatory conditions. Its contribution to inflammation was so far restricted to the nervous system and exclusively attributed to its role during leukocyte migration. We hypothesized a proinflammatory role for Ninj1 also outside the nervous system. To elucidate its impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 36 publications
9
39
0
Order By: Relevance
“…Endothelial cell activation and inflammation is the initial and critical step in the process of atherosclerosis [27,28], and our results showed that overexpression of NINJ2 can exacerbate the systemic activation and inflammation of the endothelial. Two recent studies have reported that NINJ1 can regulate the LPS-induced inflammatory response in macrophages and endothelial [25,29], which is consistent with our current findings and supports our data for further step.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
See 1 more Smart Citation
“…Endothelial cell activation and inflammation is the initial and critical step in the process of atherosclerosis [27,28], and our results showed that overexpression of NINJ2 can exacerbate the systemic activation and inflammation of the endothelial. Two recent studies have reported that NINJ1 can regulate the LPS-induced inflammatory response in macrophages and endothelial [25,29], which is consistent with our current findings and supports our data for further step.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…5B). To further prove that the transcription factor c-jun can directly binding to the first intron of NINJ2, an EMSA was performed using a double-stranded oligonucleotide encompassing the region from Previous studies have shown that NINJ1 can modulate the activation of the activator protein-1 (AP-1), which is comprised of a c-jun homodimer or a c-jun/fos heterodimer [25]. Here we investigated whether NINJ2 can regulate c-jun in a similar way.…”
Section: Cross-regulation Between Ninj2 and The Transcription Factor mentioning
confidence: 99%
“…CD93 may have a protective role in autoimmune encephalomyelitis via the control of the severity of inflammation, apoptosis and bystander neuronal injury [68]. NINJ1 is a transmembrane protein expressed primarily in myeloid and endothelial cells [69] but it was first described in the peripheral nervous system inducing neurite extension. In the latter context, NINJ1 was found to be involved in the immune pathogenesis of multiple sclerosis [70].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reveal that besides the nervous system, Ninj1 regulates several inflammatory diseases. Ninj1 inhibition reduces susceptibility to systemic inflammation, liver damage, and pulmonary inflammation in septic mice [4]. In addition, we have previously reported that Ninj1-deficient mice display a mild lung pulmonary fibrosis phenotype associated with the interaction between macrophages and alveolar epithelial cells [5].…”
Section: Introductionmentioning
confidence: 95%
“…After triggering of this complex cascade, macrophages produce pro-inflammatory cytokines and chemokines to amplify the inflammatory signal and recruit leukocytes to the lesion site. Ninj1 is reported to modulate the TLR4 signaling cascade, resulting in increased pathogenesis in septic mice [4]. Abundant studies have demonstrated that lipopolysaccharides (LPS) activate TLR families and PKC isoforms [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%